Associations of blood mercury and fatty acid concentrations with blood mitochondrial DNA copy number in the Seychelles Child Development Nutrition Study. (March 2019) - Xu, Yiyi; Wahlberg, Karin; Love, Tanzy M.; Watson, Gene E.; Yeates, Alison J.; Mulhern, Maria S.; McSorley, Emeir M.; Strain, J.J.; Davidson, Philip W.; Shamlaye, Conrad F.; Rand, Matthew D.; Myers, G.J.; et al.
Abstract: Background: Fish contains methylmercury (MeHg) which can cause oxidative stress and neurodevelopmental toxicity at sufficiently high doses. Fish also contains polyunsaturated fatty acids (PUFA) which have both antioxidant (n-3) and oxidant (n-6) properties. Mitochondrial DNA (mtDNA) is sensitive to oxidative stress but has not been previously studied in relation to MeHg exposure or PUFA status. Objective: To investigate the associations between MeHg exposure and PUFA status during pregnancy with relative mitochondrial DNA copy number (RmtDNAcn) in mothers and their newborns. Methods: In total, 1488 mother-child pairs from the Seychelles Child Development Study Nutrition Cohort 2 were included in this study. Total Hg was measured in maternal blood collected at 28 weeks' gestation, maternal hair at delivery, and in fetal cord blood. PUFA (n-3 and n-6) were measured only in maternal blood. RmtDNAcn was measured by qPCR in both maternal and cord blood. Results: Increasing maternal blood Hg (β = 0.001, 95%CI: 0.000, 0.002) and n-3 PUFA concentrations (β = 0.183, 95%CI: 0.048, 0.317) were associated with higher maternal RmtDNAcn. Increasing maternal n-6 PUFA (β = −0.103, 95%CI: −0.145, −0.062) and n-6/n-3 ratio (β = −0.011, 95%CI: −0.017, −0.004) were associated with lower maternal RmtDNAcn. Increasing fetal cord blood Hg was associated with lower fetal RmtDNAcn (β = −0.002, 95%CI: −0.004, −0.000). Neither maternal blood Hg nor PUFA status was associated with fetal RmtDNAcn. Conclusions: Our findings suggest that MeHg and PUFA may influence mitochondrial homeostasis although the magnitude of these associations are small. Future studies should confirm the findings and explore the underlying mechanisms. Highlights: We investigated, the associations between MeHg exposure, PUFA status and mtDNA copy number in a large mother-child cohort Maternal blood Hg and n-3 PUFA were positively associated with maternal mtDNA copy number Maternal blood n-6 PUFA and n-6/n-3 ratio were negatively associated with maternal mtDNA copy number Fetal cord blood Hg was negatively associated with fetal mtDNA copy number MeHg and PUFA seem to influence mitochondrial homeostasis